Adult and Continuing Education in Cyprus - Gravani, Maria (Länderporträts, 2014)
The volume offers a current stock-take of central areas of adult education in Cyprus. Maria Gravani and Alexandra Ioannidou have compiled large amounts of data and information on institutions, financing, offers, participation, personnel, quality assurance and certification. The authors furthermore take into account the political, geopolitical and cultural context which influences developments in adult education, as well as the economic situation of the island state Cyprus. This book offers a great starting point and good orientation for getting to know the Cypriotic system for adult and vocational further education.